Benzylated Sulfamethoxazole Derivatives with Improved Safety Profile as Potential Anti-Mycobacterium tuberculosis and Antibacterial Agents - Judas M. Maepa; Tlabo C. Leboho (Journal of Chemistry)
This study focussed on the synthesis of sulfamethoxazole derivatives and their biological evaluation. The sulfamethoxazole derivatives were successfully biologically evaluated against Mycobacterium tuberculosis, Staphylococcus aureus, and Chinese Hamster Ovarian (CHO) cells. The biological evaluation revealed compounds with improved antitubercular activity and antibacterial activity against S. aureus as well as safety profile when compared to the starting material, sulfamethoxazole. The most active compounds against Mycobacterium tuberculosis were3q with 92% inhibition followed by 3s (90%), 3k (88%), 3t (85%), and 3o (84%).